Constructing payments for ecosystem services hydrosocial territories through assemblage practices: China's Xin'an river basin eco-compensation pilot. (March 2023) - Sheng, Jichuan; Han, Xiao
This study employs the case of China's Xin'an River Basin Eco-compensation Pilot to explore how the payments for ecosystem services (PES) can configure local water control arenas through various assemblage practices. The findings demonstrate that specific assemblage practices can construct a PES hydrosocial territory, which often reflects power struggles. We argue that the dynamic assemblage practices redefine the boundaries of the PES hydrosocial territory and trigger the reconfiguration of PES scalar territory. Finally, we draw attention to the critical role that state intervention plays in constructing China's PES hydrosocial territory, reflecting China's remarkable governance rationality and technology. Therefore, beyond the existing interpretation of PES hydrosocial territory, the analysis of the remaking of the Xin'an River Basin has promoted the study of hydropolitics to understand better the role of assemblage practices in PES hydrosocial territory.